How to break the arbitrator's trust dilemma? - Xi, Zhang; Ab Rahman, Rozanah; Ambaras Khan, Hanna (Human Resource Management Academic Research Society, 2023)
In solving the trust-shaping problem of the investment dispute settlement mechanism, one must overcome the arbitrator’s dilemma of trust. For a long time, the arbitrator’s independence, representativeness and professionalism have suffered from being questioned, thus a series of international societies covering the code of conduct was gradually launched, and conflict of interest has ruled arbitrator, the selection and appointment mechanism. While the systemic reform to promote the judge’s jurisdiction in harmony with the host country’s regulation rights relationship issues have also appeared in a different reform path. At the bilateral level between China and the EU, the possibility exists for China to accept the EU investment tribunal model, while at the broader bilateral and multilateral levels, China should adopt a balanced stance, that is, to be wary of the risk of over-politicization that may arise from the transfer of the power to appoint arbitrators. Aside from that, China also has to prevent the abuse of regulatory power in the process of harmonizing adjudicative and regulatory powers and may consider adopting a mandatory roster system of arbitrators led by an independent third-party body and a system for the selection of members of the appellate body.